Ye heart of a man : the domestic life of men in colonial New England - Wilson, Lisa, 1957- (Yale University Press, 1999)
This book is the first to investigate the everyday lives of men in prerevolutionary America. It looks at men and women in colonial Massachusetts and Connecticut, comparing their experiences in order to understand the domestic environment in which they spent most of their time. Lisa Wilson tells wonderful stories of colonial New England men, addressing the challenges of youth, the responsibilities of adulthood, and the trials of aging. She finds that ideas about patriarchy or nineteenth-century notions of separate spheres for men and women fail to explain the world that these early New England men describe. Patriarchal power, although certainly real enough, was tempered by notions of obligation, duty, and affection. These men created their identities in a multigendered, domestic world. A man was defined by his usefulness in this domestic context; as part of an interdependent family, his goal was service to family and community, not the self-reliant independence of the next century's "self-made" man